Preparation and Characterization of SrFe12O19/rGO and SrFe12O19/SiO2 based Composite Materials for Enhancement of Microwave Absorption Properties - Thi Viet Nga, Tran; Loan, To Thanh; Quang, Nguyen Van (VNU Journal of Science: Mathematics - Physics, 2024)
In this work, we synthesized and investigated the microwave absorption properties of SrFe 12 O 19 , SrFe 12 O 19 /rGO and SrFe 12 O 19 /SiO 2 materials prepared by chemical method. The phase structure, surface morphology, magnetic properties, and electromagnetic wave absorption characteristics of the samples were studied and compared. The SEM images of SrFe 12 O 19 /rGO sample showed a good stability in the distribution and dispersion of SrFe 12 O 19 nanoparticles on rGO sheets. For SrFe 12 O 19 /SiO 2 composite samples, it is shown that SiO 2 coating is enwrapped on the SrFe 12 O 19 surface, forming SrFe 12 O 19 /SiO 2 nanocomposites with core-shell structure. The average particle size was found in the range of 60 – 120 nm. The composite SrFe 12 O 19 /rGO sample exhibited a minimum reflection loss reached -56.21 dB at 18 GHz with EAB of 12 GHz with a thickness of 3.5 mm. One can suggest that composite SrFe 12 O 19 /rGO materials possessing a best performance in both reflectivity and bandwidth can be used in the field of microwave absorption.